Safe Medicine Administration Counseling for Pregnant and Breastfeeding Mothers - Nurhidayati Harun; Firdawati Firdawati; Nia Kurniasih (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
The use of drugs for pregnancy and breastfeeding needs to be self-medication and the importance of counselling to increase the mother's knowledge about the correct use of drugs so that pregnant and lactating women's level of health and knowledge increases. The counselling purpose was to determine the mother's level of knowledge and whether there was a difference in the knowledge level of the use of drugs during pregnancy and lactation. The method used is pre and post-media analysis (flipchart). Data analysis obtain by scoring questionnaires, univariate analysis, and statistical analysis. Mann-Whitney test results showed that in the post-test or after giving counselling using flipchart media, there was a change in respondents' knowledge from before being given a flipchart and after being given a flipchart. The hypothesis from this counselling is accepted, which means that giving flipcharts affects the level of knowledge. The calculations using the spearman test obtained p-value pretest 0.732 and p-value post-test 0.253 for pregnant women and obtained p-value pretest and post-test of 0.033 (p <0.05) for breastfeeding mothers, then there is a relationship between the education level pregnant and lactating mothers with knowledge. The Wilcoxon test data pretest and post-test knowledge of pregnant and lactating mothers had a p-value of 0.003 (p 0.05), the effect of counselling concluded with flipchart media on the knowledge of pregnant and lactating mothers about the use of drugs.